2007
DOI: 10.1890/06-1032.1
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Viable Metapopulation Size, Extinction Debt, and the Conservation of a Declining Species

Abstract: A key question facing conservation biologists is whether declines in species' distributions are keeping pace with landscape change, or whether current distributions overestimate probabilities of future persistence. We use metapopulations of the marsh fritillary butterfly Euphydryas aurinia in the United Kingdom as a model system to test for extinction debt in a declining species. We derive parameters for a metapopulation model (incidence function model, IFM) using information from a 625-km2 landscape where hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 50 publications
(77 reference statements)
7
103
0
Order By: Relevance
“…If the surrounding landscape is being managed and colonies survive nearby, it will probably recolonize naturally in due course. (Anthes et al 2003a;Anthes et al 2003b;Anthes and Nunner 2006;Barnett and Warren 1995;Betzholtz et al 2007;Botham et al 2011;Bulman et al 2007;Hula et al 2004;Joyce and Pullin 2003;Junker and Schmitt 2010;Konvička et al 2003;Liu et al 2006;Munguira et al 1997;Porter and Ellis 2011;Saarinen et al 2005;Schtickzelle et al 2005;Smee et al 2011;Stefanescu et al 2006;Wang et al 2004;Warren 1994;Warren et al 1994;Zimmermann et al 2011a;Zimmermann et al 2011b)…”
Section: Euphydryas Aurinia Dosmentioning
confidence: 99%
“…If the surrounding landscape is being managed and colonies survive nearby, it will probably recolonize naturally in due course. (Anthes et al 2003a;Anthes et al 2003b;Anthes and Nunner 2006;Barnett and Warren 1995;Betzholtz et al 2007;Botham et al 2011;Bulman et al 2007;Hula et al 2004;Joyce and Pullin 2003;Junker and Schmitt 2010;Konvička et al 2003;Liu et al 2006;Munguira et al 1997;Porter and Ellis 2011;Saarinen et al 2005;Schtickzelle et al 2005;Smee et al 2011;Stefanescu et al 2006;Wang et al 2004;Warren 1994;Warren et al 1994;Zimmermann et al 2011a;Zimmermann et al 2011b)…”
Section: Euphydryas Aurinia Dosmentioning
confidence: 99%
“…For a similar taxonomic group, butterflies, the available empirical evidence for delayed population response to habitat loss is mixed with some studies reporting rather fast (several years) (12,27) and others relatively long (several decades or more) relaxation times (17). In addition, theoretical simulations have suggested that the delay in insect metapopulation extinctions can extend well beyond 100 y (28), and that their lag times are particularly long if available habitat networks are reduced to levels close to the extinction threshold (29), as might be the case in many landscapes of Europe where an intensively used agricultural matrix is interspersed by remnants of near-natural and nonintensively used habitats (30).…”
Section: Discussionmentioning
confidence: 99%
“…Habitat patch networks may undergo gradual degradation (Mortelliti et al 2010) or loss (Bulman et al 2007) of habitat patches because of human land use activities. Additionally, climate change may cause habitat patch networks to shift gradually toward the poles (Radchuck et al 2014).…”
Section: Conservation Of Dynamic Habitat Networkmentioning
confidence: 99%